VERBS OF VERTICAL MOVEMENT WITH THE SEMANTICS "TO FALL" IN THE KHANTY LANGUAGE - F. M. Lelkhova; Ф. М. Лельхова (Кемеровский государственный университет, 2016)
The paper studies the dialect material of the Khanty language: the semantic structure of the verbs of vertical movement, namely the verbs of motion with the meaning «to fall». Each particular meaning of a polysemantic verb is connected to the other meanings with the same seme, and at the same time differs by semantic structure and the components constituting its meaning. В данной работе на диалектном материале хантыйского языка исследуется семантическая структура глаголов вертикального движения, а именно глаголов движения со значением «падать». Каждое отдельное значение многозначного глагола связано с другими значениями общей семой и в то же время отличается семантической структурой, составом компонентов, из которых складывается его содержание.